A ação regressiva acidentária como instrumento de tutela do meio ambiente do trabalho - Zimmermann, Cirlene Luiza (My University, 2014)
The environment of work and the regressive action related accidents are the objects of the present study. The sound environment, including that of the work, is handled by the Federal Constitution of 1988 as a fundamental right, essential to the implementation of the basic principle of human dignity, to be obtained with the enjoyment of a healthy quality of life. For this reason, several instruments are available by standing order for the protection of that right. The action regressive related accidents, under art. 120 of Law No. 8.213/91, is one such instruments. However, had long been virtually ignored by social security, as a holder of the right/duty to return, an omission which, fortunately, have been suppressed in recent years by the actions of the Attorney General´s Office, through the Federal Attorney General, which issued regressive action related accidents among its priority actions. The society, by ignoring the institute, also did not charge its use, despite its potential for protection of the right of workers to perform their working activities in safe and healthy, coming mainly from its pedagogical-punitive. About the social values of work is based on our Republic and the exercise of their professional activities is indispensable to the citizens for the consolidation of that right. But not just any job, but he played under appropriate conditions, without risk, to ensure the life, health and physical and mental health workers, because only with the care of these assumptions is that the actual principle of the dignity of human person. Official statistics about accidents at work in Brazil, although only reflect the framework of formal employment, they show real affront to the fundamental right to work, balanced environment, the work included therein, and human dignity. The environmental principles play an important role in controlling workplace risks, why should serve as guidance to all those responsible for overseeing the work environment in their continuing work to improve conditions in this environment. Moreover, the constitutional principles of economic order must be reconciled with the fundamental right to a balanced environment, which also happens to be a collective duty. The classic institute of liability needs to be reformulated before it can be satisfactorily applied in the environmental sphere and that goes beyond mere pacification about its impact on the objective modality. The duty to assume responsibility for environmental risks must be anticipated to action, to avoid the consequences of which traditionally falls on the institute. The work performed in the right environment is worthy to be guaranteed to all workers, regardless of the means of formalizing the working relationship and the size of the company in which it is exercised, not serving the payment of insurance against accidents at work as authorization for dereliction of duty. The development of public policies on the environment of work, as well as the detailed study of their instruments of protection, as is the case of the regressive action related accidents, it is essential to guarantee the right.
O meio ambiente do trabalho e a ação regressiva acidentária são os objetos de estudo do presente trabalho. O meio ambiente equilibrado, nele compreendido o do trabalho, é tratado pela Constituição Federal de 1988 como direito fundamental, indispensável à concretização do princípio-base da dignidade da pessoa humana, a ser obtida com o usufruto de uma sadia qualidade de vida. Por tal razão, diversos instrumentos jurídicos são disponibilizados pela ordem vigente para a tutela desse direito. A ação regressiva acidentária, prevista no art. 120 da Lei nº 8.213/91, é um desses instrumentos. Todavia, durante muito tempo foi praticamente ignorada pela Previdência Social, enquanto titular do direito/dever de regresso, omissão que, felizmente, vem sendo suprimida nos últimos anos pela atuação da Advocacia-Geral da União, através da Procuradoria-Geral Federal, que inseriu a ação regressiva acidentária entre suas ações prioritárias. A sociedade, por desconhecer o instituto, também não cobrava sua utilização, apesar do seu potencial de tutela do direito dos trabalhadores de exercerem suas atividades laborais em ambientes seguros e salubres, advindo, principalmente, do seu caráter pedagógico-punitivo. Sobre os valores sociais do trabalho fundamenta-se nossa República, sendo o exercício de atividades laborais elemento indispensável aos cidadãos para a consolidação desse direito. Contudo, não se trata de qualquer trabalho, mas aquele desempenhado em condições adequadas, sem riscos, que garanta a vida, a saúde e a integridade física e mental dos trabalhadores, pois somente com o atendimento desses pressupostos é que se efetiva o princípio da dignidade da pessoa humana. As estatísticas oficiais sobre os acidentes do trabalho no Brasil, ainda que só reflitam o quadro do emprego formal, evidenciam verdadeira afronta ao direito fundamental ao trabalho, ao meio ambiente equilibrado, nele incluído o do trabalho, e à dignidade da pessoa humana. Os princípios ambientais exercem importante papel no controle dos riscos laborais, motivo pelo qual devem servir de orientação a todos os responsáveis pela tutela do ambiente do trabalho em sua tarefa contínua de melhorar as condições desse meio. Por outro lado, os princípios constitucionais da ordem econômica precisam ser compatibilizados com o direito fundamental ao meio ambiente equilibrado, que vem a ser também um dever da coletividade. O clássico instituto da responsabilidade civil necessita ser reformulado para poder ser aplicado satisfatoriamente na esfera ambiental e isso vai além da mera pacificação acerca da sua incidência na modalidade objetiva. O dever de assumir as responsabilidades pelos riscos ambientais deve ser antecipado à ação, de modo a evitar as consequências sobre as quais tradicionalmente recai o instituto. O exercício do trabalho em ambientes dignos é direito que deve ser garantido a todos os trabalhadores, independentemente do meio de formalização da relação de trabalho e do tamanho da empresa em que ele é exercido, não servindo o pagamento do seguro contra acidentes de trabalho como autorização para o descumprimento do dever. O desenvolvimento de políticas públicas em prol do meio ambiente do trabalho, assim como o estudo aprofundado dos seus instrumentos de tutela, como é o caso da ação regressiva acidentária, é essencial para garantir o direito.
Keywords: Direito; Meio ambiente do trabalho; Riscos; Direito fundamental; Princípios constitucionais; Tutela; Responsabilidade civil; Ação regressiva acidentária; Segurança do trabalho; Prevenção de acidentes; Working environment; Risks; Fundamental rights; Constitutional principles; Guardianship; Liability; Regressive action related accidents; Industrial safety; Accidents - Prevention